2014
DOI: 10.1073/pnas.1402289111
|View full text |Cite
|
Sign up to set email alerts
|

Duration of urination does not change with body size

Abstract: Many urological studies rely on models of animals, such as rats and pigs, but their relation to the human urinary system is poorly understood. Here, we elucidate the hydrodynamics of urination across five orders of magnitude in body mass. Using high-speed videography and flow-rate measurement obtained at Zoo Atlanta, we discover that all mammals above 3 kg in weight empty their bladders over nearly constant duration of 21 ± 13 s. This feat is possible, because larger animals have longer urethras and thus, high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 58 publications
0
52
0
Order By: Relevance
“…9). A cross-species analysis has shown that this is a typical voiding duration [26], suggesting that we were observing a physiological process, even under sedation. This is in contrast to anesthetized voiding sessions which have reported similar voided amounts across longer durations (1–3 minutes) [27,28].…”
Section: Discussionmentioning
confidence: 89%
“…9). A cross-species analysis has shown that this is a typical voiding duration [26], suggesting that we were observing a physiological process, even under sedation. This is in contrast to anesthetized voiding sessions which have reported similar voided amounts across longer durations (1–3 minutes) [27,28].…”
Section: Discussionmentioning
confidence: 89%
“…The example is derived from one of the author's (Hu) Ig Nobel‐prize‐winning paper on the fact that most animals urinate for approximately the same duration (21 s on average) (Yang et al, ). The research was motivated by a rather unfortunate experience of the author changing his son's diapers.…”
Section: Discussionmentioning
confidence: 99%
“…All other projects showed no statistical difference between the mean of the other projects several important skills for scientific and engineering inquiry and problem solving. The example is derived from one of the author's (Hu) Ig Nobel-prize-winning paper on the fact that most animals urinate for approximately the same duration (21 s on average) (Yang et al, 2014). The research was motivated by a rather unfortunate experience of the author changing his son's diapers.…”
Section: Using Urination To Humorously Teach Engineering and Biologymentioning
confidence: 99%
“…Moreover, rodent bladders differ from those of humans functionally. While larger mammals (>3Kg) share a scalable urinary capacity and consistent voiding duration, rodents urinate almost constantly, bringing into question whether their bladders are a true storage organ 37 . The multiple disparities between the rodent and human bladders raise the possibility that relying so heavily on the former could be problematic for understanding UTI in the latter.…”
Section: Introductionmentioning
confidence: 99%